Variabilidade da qualidade da água e do estado trófico do reservatório do Vacacaí Mirim - Burin, Rodrigo (2011)
The construction of several reservoirs to meet multiple uses has become essential to human societies. The Vacacaí Mirim s reservoir is used primarily for human supply, accounting for 40% of the Santa Maria water supply. The exam of this reservoir provides a fundamental basis for managing its water quality and its watershed. The objective of this research is to evaluate the variability of the water quality and the trophic status of the Vacacaí Mirim s reservoir. Eight field campaigns were performed between 2010 and 2011, and the water samples were taken at four distributed points along the reservoir and one point located upstream the main tributary river. On the reservoir s sampling points were collected samples from surface (S) and depth (P). The main water quality parameters evaluated were: Water Temperature, pH, Electrical Conductivity, Turbidity, DO, BOD5, COD, TSS, TDS, E. coli, Chlorophyll-a, Ammonium, Nitrite, Nitrate, Total Phosphorus. The trophic status was monitored considering the levels of phosphorus, chlorophyll-a and some biological indicators. The Vacacaí Mirim s reservoir presented a long period of thermal stability, being more or less consistent to the seasonal period, with full circulation only in winter, conferring its classification as warm monomictic. The concentration of most parameters analyzed varied more on a time level than a space level. The parameter that inspires greater concern is the number of E. coli, which in 16% of the time exceeds the limits for class 3 of CONAMA Resolution No. 357/05 making the water unsuitable for this purpose. The correlation analysis also showed strong relationship between some environmental hydrological variables with some parameters of quality. The seasonal variation of the values of the TSI and biological indicators, suggest the Vacacaí Mirim s reservoir as a mesotrophic ecosystem, sometimes tending to eutrophic, so showing an anthropogenic influence. It is suggested to the government, organizations and population, the proper attention to the degradation processes, being necessary the watershed land use control and ordination, the riparian vegetation reestablishment, as well as an adjustment on the effluents emission through appropriate treatment.